ERA (Evidence for Resilient Agriculture) Feed Library - Muller, Lolita; Steward, Peter Richard; Joshi, Namita; Nabwire, Charity Ephamia Juma; Rosenstock, Todd Stuart (2025)
The ERA Feed Library is an analysis-ready reference dataset for livestock nutrition, covering more than 1,200 feed ingredients spanning forages, grains, by-products, legumes, shrubs, tree leaves, and grasses, including multiple processing forms. It consolidates manually extracted data from over 700 livestock nutrition studies across Africa and harmonizes ingredient naming using the AOM classification.